Secret faith in the public square: an argument for the concealment of Christian identity - Malesic, Jonathan (Brazos Press, 2009)
Secrecy and Christian faith in contemporary America -- Promoting secrecy in a Christian empire : Cyril of Jerusalem's discipline of the secret -- Liturgical secrecy as Cyril's defense against opportunism and imperial authority -- The secret of faith in Kierkegaard's Works of love -- How Kierkegaard's secret agape subverts bourgeois culture -- Bonhoeffer's Arkandisziplin : Christian confession in a world come of age -- The limits of Arkandisziplin and of the secular -- The secret-keeping self and Christian responsibility for the other -- The church as a community of hidden disciples -- Secret faith's fulfillment of the church's mission in America : an engagement with Hauerwas -- The challenge of ambiguous religious identity in Wise blood and The moviegoer